Salinomycin overcomes ABC transporter-mediated multidrug and apoptosis resistance in human leukemia stem cell-like KG-1a cells - Fuchs, Dominik; Daniel, Volker; Sadeghi, Mahmoud; Opelz, Gerhard; Naujokat, Cord (Biochemical and biophysical research communications, 2010)
Leukemia stem cells are known to exhibit multidrug resistance by expression of ATP-binding cassette (ABC) transporters which constitute transmembrane proteins capable of exporting a wide variety of chemotherapeutic drugs from the cytosol. We show here that human promyeloblastic leukemia KG-1a cells exposed to the histone deacetylase inhibitor phenylbutyrate resemble many characteristics of leukemia stem cells, including expression of functional ABC transporters such as P-glycoprotein, BCRP and MRP8. Consequently, KG-1a cells display resistance to the induction of apoptosis by various chemotherapeutic drugs. Resistance to apoptosis induction by chemotherapeutic drugs can be reversed by cyclosporine A, which effectively inhibits the activity of P-glycoprotein and BCRP, thus demonstrating ABC transporter-mediated drug resistance in KG-1a cells. However, KG-1a are highly sensitive to apoptosis induction by salinomycin, a polyether ionophore antibiotic that has recently been shown to kill human breast cancer stem cell-like cells and to induce apoptosis in human cancer cells displaying multiple mechanisms of drug and apoptosis resistance. Whereas KG-1a cells can be adapted to proliferate in the presence of apoptosis-inducing concentrations of bortezomib and doxorubicin, salinomycin does not permit long-term adaptation of the cells to apoptosis-inducing concentrations. Thus, salinomycin should be regarded as a novel and effective agent for the elimination of leukemia stem cells and other tumor cells exhibiting ABC transporter-mediated multidrug resistance.
Gesehen am 17.07.2023